BENTUK DAN MAKNA EMOSI DALAM CERITA KODA RAGAPM SASTRA LISAN DAYAK SIMPAKNG DI KABUPATEN KETAPANG - Alberta Alberta; Parlindungan Nadeak; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem in this study is the form of verbal emotion and meaning contained inthe story of Koda Ragapm, Dayak oral literature in Ketapang Regency and theform of nonverbal emotion and meaning contained in the story of Koda Ragapm,Dayak oral literature in Ketapang Regency. The method in this research isdescriptive qualitative method. The results of this study are the emotions containedin the story of Koda Ragapm, namely verbal and nonverbal emotions, the emotionsin which are divided into three namely positive, negative and mixed emotions. Soin the story of Koda Ragapm there are nine positive verbal emotions, four negativeverbal emotions, and seven mixed emotions. The nonverbal emotions contained inthe Koda Ragapm story are three positive emotions, one negative emotion, andone mixed emotion. The emotions contained in the Damamakng Balayar storyhave two positive emotions, two negative emotions and eight mixed emotions. Thenonverbal emotions contained in the story of Damamakng Balayar are fivepositive emotions. The emotions contained in Damia Podi's story are threepositive emotions, one negative emotion and one mixed emotion. Mixed emotions.The nonverbal emotions contained in Damia Podi's story are one positive emotionand one negative emotion.Keywords: Forms and Meanings of Emotions, Koda Ragapm, DayakSimpakng